The viability of developing Maori leasehold land : the case of Part XXIII hill country leases in the Tairawhiti land district : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Economics at Massey University - Tattersfield, Georgina Maree Iritana (Massey University, 1983)
This Thesis is concerned with assessing the extent of underutilization and reversion that has occurred on land leased under the provisions of Part XXIII of the 1953 Maori Affairs Act. It seeks to determine the constraints that exist to the development of Part XXIII leases. Further it attempts to find ways to overcome these constraints, that are compatible with the needs of the Maori people. Chapter One of this thesis discusses the reasons for this study. It outlines the objects of the study and reviews the design of research used to obtain these objects. Chapter Two deals with the selection of a sample of Part XXIII leases to be studied and assesses their relative states of development. Chapter Three describes the Tairawhiti Land District, the farm environment in which the lease sample exists. Chapter Four reviews the evolution of Maori Land Tenure and discusses the institutional and administrative problems that have resulted from changes in it. This chapter identifies 438/53 trusts and incorporations as modes of administration for Maori land that are more compatible, than Part XXIII of the 1953 Act, with the ancient ideals of the Maori people. Chapter Five identifies specific institutional, physical, financial and management factors that can constrain the development of Part XXIII leases. Chapter Six analyses the relationship between specific factors throught to constrain Part XXIII lease farm development and actual states of development on the sample leases. Chapter Seven draws conclusions on the analysis done in Chapter Six and makes recommendations on ways to promote the farm development of land presently leased under the provisions of Part XXIII of the 1953 Maori Affairs Act.
Keywords: New Zealand; Maori; Land tenure; Law and legislation; Economic conditions